How Emotion Relates to Language and Cognition, Seen Through the Lens of Evaluative Priming Paradigms - Rohr, Michaela; Wentura, Dirk (Frontiers in Psychology, 2022)
Affect and emotion are essential aspects of our human life. These concepts, states or feelings signal personally relevant things, situations, inner conditions, memories, or imaginations. Within this area of affective or emotion processing, evaluation, that is, the assessment of the valence associated with a stimulus or event (i.e., its positivity or negativity), is considered a basic process, an early step in constructivist emotion theories, and perhaps the most important one after all. It is assumed to occur automatically when encountering a stimulus. But does it really? Even if we simply see a word? And if so, what exactly is processed or activated in memory? One approach to investigate this evaluative aspect are behavioral priming paradigms, and first and foremost the evaluative priming paradigm and its variants. In the present review we delineate the insights gained with this paradigm about the relation of affect and emotion to cognition and language. Specifically, we review the empirical evidence base with regard to this issue as well as the proposed theoretical models for the representations activated via such paradigms. It will become clear that affect and emotion are only triggered via evaluative priming paradigms in the sense that semantic affective knowledge is activated. The emerging evidence concerning the processing of more specific emotion aspects gives, however, rise to the assumption that the activation of these aspects is related to their social importance. In that sense, the fast and (conditionally) automatic activation of valence and other emotion aspects in evaluative priming paradigms reveals something about affect and emotion: Valence and specific emotion aspects are so important for our daily life that the encountering of almost every stimulus entails the automatic activation of the associated valence and other emotion aspects when the context requires it.